2020
DOI: 10.1097/mpa.0000000000001635
|View full text |Cite
|
Sign up to set email alerts
|

Depression Before and After a Diagnosis of Pancreatic Cancer

Abstract: Objectives The aim of this study was to evaluate depression in pancreatic cancer (PC) patients before and after a cancer diagnosis using a US-based healthcare database. We also sought to study the impact of treatment of depression in PC patients on all-cause mortality. Methods Pancreatic cancer patients with comorbid depression in Explorys (1999–2019) were compared with controls using odds ratios with 95% confidence intervals. Rates of depression diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Of note, a recent report demonstrated that over 90% of patients diagnosed with depression in the year preceding diagnosis of PC were diagnosed in the 6-month period immediately preceding identification of PC. 12 Prediagnosis depression and anxiety were not recorded when documentation stated that these conditions were secondary to the diagnostic work-up or knowledge of PC.…”
Section: Depression and Anxiety Diagnosesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of note, a recent report demonstrated that over 90% of patients diagnosed with depression in the year preceding diagnosis of PC were diagnosed in the 6-month period immediately preceding identification of PC. 12 Prediagnosis depression and anxiety were not recorded when documentation stated that these conditions were secondary to the diagnostic work-up or knowledge of PC.…”
Section: Depression and Anxiety Diagnosesmentioning
confidence: 99%
“…[5][6][7][8] Patients with PCassociated depression or anxiety suffer worse outcomes, including a poor quality of life, reduced compliance with treatment, 3,[9][10][11] and reduced survival. 11,12 Thus, effective mental health screening and treatment of psychiatric symptoms may have important oncologic ramifications. 12 Physicians may underappreciate that PC is frequently foreshadowed by depression or anxiety, similar to presenting signs like unintentional weight loss or new-onset or worsening diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several forums were subsequently presented by Kenner Family Research Fund, including the 2015 Early Detection of Pancreatic Cancer: Lessons Learned from Other Cancers 6 and the 2016 The Role of Industry in the Development of Biomarkers . 7 In 2018, the Role of Depression and Anxiety as a Precursor for Disease 8 , 9 was the core presentation in a symposium at the American Pancreatic Association. After these initiatives and the publication of several articles for dissemination to the broader community, significant additional funding was invested in early detection research.…”
mentioning
confidence: 99%